ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN SEKTOR KESEHATAN DI KABUPATEN KUTAI KARTANEGARA - Muhammad Risal (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This paper try to seek informations about the public service satisfaction in Kutai Kartanegara Regency especially on public health service. This research is a descriptive one and use likert scale that is a standard method to scale public service satisfaction. The result shows that in general public health service in Kutai Kartanegara Regency is on the good scale and already on track with the local government’s expectation.Keywords: Public Service Satisfaction, Public Health, Kutai Kartanegara